Superior performance of continuous over pulsatile flow ventricular assist devices in the single ventricle circulation: A computational study. (8th February 2017) - Schmidt, Tyler; Rosenthal, David; Reinhartz, Olaf; Riemer, Kirk; He, Fei; Hsia, Tain-Yen; Marsden, Alison; Kung, Ethan; ,
Abstract: This study compares the physiological responses of systemic-to-pulmonary shunted single ventricle patients to pulsatile and continuous flow ventricular assist devices (VADs). Performance differences between pulsatile and continuous flow VADs have been clinically observed, but the underlying mechanism remains poorly understood. Six systemic-to-pulmonary shunted single ventricle patients (mean BSA=0.30 m 2 ) were computationally simulated using a lumped-parameter network tuned to match patient specific clinical data. A first set of simulations compared current clinical implementation of VADs in single ventricle patients. A second set modified pulsatile flow VAD settings with the goal to optimize cardiac output (CO). For all patients, the best-case continuous flow VAD CO was at least 0.99 L/min greater than the optimized pulsatile flow VAD CO ( p =0.001). The 25 and 50 mL pulsatile flow VADs exhibited incomplete filling at higher heart rates that reduced CO as much as 9.7% and 37.3% below expectations respectively. Optimization of pulsatile flow VAD settings did not achieve statistically significant ( p <0.05) improvement to CO. Results corroborate clinical experience that continuous flow VADs produce higher CO and superior ventricular unloading in single ventricle patients. Impaired filling leads to performance degradation of pulsatile flow VADs in the single ventricle circulation.